Prevalence and determinants of breast cancer screening in four sub-Saharan African countries: a population-based study. Issue 10 (12th October 2020) - Ba, Djibril M; Ssentongo, Paddy; Agbese, Edeanya; Yang, Yanxu; Cisse, Ramata; Diakite, Brehima; Traore, Cheick Bougadari; Kamate, Bakarou; Kassogue, Yaya; Dolo, Guimogo; Dembele, Etienne; Diallo, Hama; et al.
Abstract : Objectives: Breast cancer is the most prevalent cancer and the second leading cause of cancer-related deaths among women after cervical cancer in much of sub-Saharan Africa. This study aims to examine the prevalence and sociodemographic–socioeconomic factors associated with breast cancer screening among women of reproductive age in sub-Saharan Africa. Design: A weighted population-based cross-sectional study using Demographic and Health Surveys (DHS) data. We used all available data on breast cancer screening from the DHS for four sub-Saharan African countries (Burkina Faso, Ivory Coast, Kenya and Namibia). Breast cancer screening was the outcome of interest for this study. Multivariable Poisson regression was used to identify independent factors associated with breast cancer screening. Setting: Four countries participating in the DHS from 2010 to 2014 with data on breast cancer screening. Participants: Women of reproductive age 15–49 years (N=39 646). Results: The overall prevalence of breast cancer screening was only 12.9% during the study period, ranging from 5.2% in Ivory Coast to 23.1% in Namibia. Factors associated with breast cancer screening were secondary/higher education with adjusted prevalence ratio (adjusted PR)=2.33 (95% CI: 2.05 to 2.66) compared with no education; older participants, 35–49 years (adjusted PR=1.73, 95% CI : 1.56 to 1.91) compared with younger participants 15–24 years; health insurance coverage (adjusted PR=1.57, 95% CI: 1.47 to 1.68) compared with those with no health insurance and highest socioeconomic status (adjusted PR=1.33, 95% CI : 1.19 to 1.49) compared with lowest socioeconomic status. Conclusion: Despite high breast cancer mortality rates in sub-Saharan Africa, the prevalence of breast cancer screening is substantially low and varies gradually across countries and in relation to factors such as education, age, health insurance coverage and household wealth index level. These results highlight the need for increased efforts to improve the uptake of breast cancer screening in sub-Saharan Africa.